Smart and Digital Cities. From Computational Intelligence to Applied Social Sciences. - (:unkn) unknown (Springer, 2019)
This book presents up-to-date information on the future digital and smart cities. In particular, it describes novel insights about the use of computational intelligence techniques and decentralized technologies, covering urban aspects and services, cities governance and social sciences. The topics covered here range from state-of-the-art computational techniques to current discussions regarding drones, blockchain, smart contracts and cryptocurrencies. The idealization of this material emerged with a journey of free knowledge exchange from a diverse group of authors, who met each other through four different events (workshops and special sessions) organized with the purpose of boosting the concepts surrounding smart cities. We believe that this book comprises innovative and precise information regarding state-of-the-art applications and ideas for the future of cities and society. It will surely be useful not only for the academic community but also to the industry professionals and city managers.
Keywords: Stadtentwicklung; Smart City; Digitalisierung; Stadtverkehr; Nahverkehrssystem; Modal Split; Wirtschaftsverkehr; Verkehrsanalyse; Verkehrsbewegung; EDV-Anwendung; Algorithmus; Entscheidungsfindung; Urban Governance; Smart Grid; Energiedienstleistung; EDV-Software; Multimodalität